2012
DOI: 10.1289/ehp.1104793
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Lead Poisoning Associated with Gold Ore Processing: a Village-Level Investigation—Zamfara State, Nigeria, October–November 2010

Abstract: Background: During May–June 2010, a childhood lead poisoning outbreak related to gold ore processing was confirmed in two villages in Zamfara State, Nigeria. During June–September of that year, villages with suspected or confirmed childhood lead poisoning continued to be identified in Zamfara State.Objectives: We investigated the extent of childhood lead poisoning [≥ 1 child with a blood lead level (BLL) ≥ 10 µg/dL] and lead contamination (≥ 1 soil/dust sample with a lead level > 400 parts per million) among v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
93
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(98 citation statements)
references
References 13 publications
3
93
1
1
Order By: Relevance
“…conducted a study in some locations in Zamfara State and reported high levels of concentration of lead in the soil. Similar studies were conducted by Lo et al (2012) and Udiba et al (2012) where high levels of concentration of lead in soils of Zamfara State were reported. In all these studies, areas of high lead concentration were reported to be part of the areas affected by the Zamfara lead poisoning crisis.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…conducted a study in some locations in Zamfara State and reported high levels of concentration of lead in the soil. Similar studies were conducted by Lo et al (2012) and Udiba et al (2012) where high levels of concentration of lead in soils of Zamfara State were reported. In all these studies, areas of high lead concentration were reported to be part of the areas affected by the Zamfara lead poisoning crisis.…”
Section: Discussionsupporting
confidence: 85%
“…Human exposure to lead is estimated to account for 143, 000 deaths every year and 0.6% of the global burden of disease (WHO, 2010). Exposure to lead affects multiple health outcomes and physiological systems, including hypertension, the gastrointestinal systems, anaemia, nephropathy, vitamin D metabolism, decreased growth, the immune system, the nervous system, behavioural/cognitive/IQ effects and as a result, multiple social effects including increased risk of violence and drug abuse, nerve conductive effects, hearing loss, effects on reproduction and development, and death from encephalopathy (O'Dwyer, 1998;Tong et al, 2000;Fewtrell et al, 2003 andPruss-Ustun et al, 2004;CDC, 2004 and2005;Battersby, 2008;Mitra et al, 2009;WHO, 2010WHO, , 2011aWHO, and 2011bDooyema et al, 2012;Lo et al, 2012;Udiba et al, 2012).…”
Section: Effects Of Lead Poisoningmentioning
confidence: 99%
“…A recent investigation in Nigeria revealed over 100 child fatalities related to lead poisoning (Dooyema et al 2011;Lo et al 2012). There are also reports of lead-related fatalities from Senegal (Haefliger et al 2009), where the World Health Organization (WHO) confirmed at least 18 children died from lead poisoning.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the past episodes of heavy metal contamination in the aquatic environment have increased the awareness about their toxicity. The outbreak of lead poison in Zamfara state, Nigeria [1,2]; the direct discharge of heavy metal containing wastes into water bodies or sewers is to be checked in order to reduce the environmental impact [3].…”
Section: Introductionmentioning
confidence: 99%